The Role of Business Incubators in Encouraging Maritime Technology Start-up Innovation - Yusup, Muhammad Firdaus Bin (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2024)
This study examines the critical role of business incubators in driving innovation in maritime technology start-ups. With the growing need for innovative technology solutions in the maritime industry, business incubators have emerged as a key catalyst in developing and introducing new ideas to the market. The study used a qualitative approach, involving in-depth interviews with 30 stakeholders, including start-up founders, incubator managers, and maritime industry experts. The results showed that business incubators provide critical support in the form of access to funding, expert mentoring, research and development facilities, and extensive industry networks. The findings also revealed that incubators that focus on the maritime sector are more effective in helping start-ups overcome industry-specific challenges. The study highlights the importance of collaboration between incubators, the maritime industry, and educational institutions to create an ecosystem that supports innovation. Implications of this study include recommendations for policymakers and industry players in designing more effective incubation programs to drive maritime technology innovation.